Economic Nature and Classification of Stablecoins - D. A. Kochergin (Финансы: теория и практика, 2020)
The article discusses the nature of stablecoins and their specifics in the financial market. The aim of the article is to reveal the economic nature and characteristics of various types of stablecoins. The author used system-functional and system-structural research methods as well as methods of statistical analysis and synthesis. The paper analyses different approaches to the interpretation of stablecoins and their regulation in developed countries, as well as provides the author’s interpretation and classification of stablecoins. The article analyses the main indicators of stablecoins and identifies the potential benefits and risks associated with payment. The conclusion is that stablecoins are to be interpreted as a new hybrid type of digital financial assets. Stablecoins are not homogeneous and may have different economic and legal characteristics. Clearly identified blockchain-based issuers issue most stablecoins as tradable digital bonds or depository receipts that can be used as a means of exchange, savings, and payment. The major economic and functional criteria for the classification of stablecoins are: the form of collateral, the category of users, and the scale of circulation. The research has shown that currently the most widely used are centralized stablecoins, backed by fiat currencies and gold, used for exchange transactions and retail payments. Local stablecoins are primarily a store of value and a medium of exchange. Their widespread use can significantly affect the development of the crypto-asset market by increasing its liquidity and stimulating the development of more stable forms of digital financial assets. Global stablecoins may gain widespread use as a cross-border means of payment. They can increase the speed of crossborder settlements and reduce their costs, as well as provide wider financial inclusion for users without bank accounts. To realize the potential benefits of stablecoins, one should address the legal, regulatory and supervisory challenges associated with national and cross-border circulation of stablecoins.